C-glycosides of dodecanoic acid: new capping/reducing agents for glyconanoparticle synthesis - Ramana, C. V.; Durugkar, Kulbhushan A.; Puranik, Vedavati G.; Narute, Sachin B.; Bhagavatula L. V. Prasad (Tetrahedron Letters, 2008)
A concise synthesis of 12-C-glycosylated dodecanoic acids employing an olefin cross-metathesis reaction is developed. Examination of these acids as capping agents for the synthesis of metal nanoparticles reveals that they do not cap the Co-metal nanoparticles synthesized in aqueous phase, but that two of them can reduce and cap the Ag nanoparticles in water without any aggregation. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: C-Glycosides; Cross metathesis; glyconanoparticles; Grubbs' catalyst; silver nanoparticles